2019
DOI: 10.2147/jbm.s177692
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ruxolitinib In The Treatment Of Polycythemia Vera: An Update On Health-Related Quality Of Life And Patient-Reported Outcomes</p>

Abstract: Polycythemia vera (PV) is a rare myeloproliferative neoplasm (MPN) associated with significant impairment in quality of life (QoL) due to disease-related symptoms and complications. Assessment of disease burden constitutes standard monitoring of symptoms and response. Conventional treatments for MPN, such as hydroxyurea, phlebotomy, or interferon, have not shown a significant impact in QoL or patient-reported outcomes (PRO). Ruxolitinib (RUX) is a JAK2 inhibitor approved for patients intolerant or resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In addition, many patients are considered pruritis as the most upsetting symptom of PV, the same with our patient. [3,4,6] The pathophysiology of PV-associated pruritis is not wellunderstood. It was found that increased mast cells in the dermis are present in PV patients with pruritis; however, a similar number has been detected in patients without pruritis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many patients are considered pruritis as the most upsetting symptom of PV, the same with our patient. [3,4,6] The pathophysiology of PV-associated pruritis is not wellunderstood. It was found that increased mast cells in the dermis are present in PV patients with pruritis; however, a similar number has been detected in patients without pruritis.…”
Section: Discussionmentioning
confidence: 99%
“…Among JAK inhibitors, ruxolitinib is currently used in patients who suffer myelofibrosis. In this hematological condition, ruxolitinib can rapidly improve the patient's quality of life by reducing the secretion of pro-inflammatory cytokines, such as IL-1, TNF-α, IFN-γ, and IL-6 [158][159][160].…”
Section: Ruxolitinibmentioning
confidence: 99%
“…Vaccination to prevent reactivation of zoster is thus advocated prior to treatment [15,18]. Evidence-based medicine has revealed the favorable potential of ruxolitinib in PV, with alleviation of symptoms and improved patient-reported outcomes and quality of life [19]. A study to uncover the potential of momelotinib (a similar JAK inhibitor) in PV was also conducted but terminated due to low efficacy [20].…”
Section: Ruxolitinibmentioning
confidence: 99%